Ultrasonic pulse velocity (UPV) test on concrete under compression : a study on effect of aspect ratio - Chai, Peng How. (Universiti Malaysia Sarawak, (UNIMAS), 2005)
This project describes a research study on the effect of aspects ratio in concrete at different levels of compressive stress on the measured of ultrasonic pulse velocity (UPV) values. Concrete prisms with grade 25 and 30 with different height/width ratio were used and tests were carried out at 28 days. The test results for concrete prisms of grade 25 and 30 showed similar trends. However, the changes of UPV values in concrete prisms of grade 30 are more significant than concrete prisms of grade 25 . It was also found that the compressive stress in concrete have more significant effect of the measured UPV values on concrete prisms with aspect ratio of 1: 1, which is the smallest height/width ratio. In general, the UPV values increased in concrete prisms at stress-strength ratio ranging from 0 to 0.25. After which, the measured UPV values reduced significantly under a higher compressive stress of up to 0.5 stress-strength ratio. When subjected to compressive stress which corresponds to a stress-strength ratio of 0.25, the UPV values increased by about 4.7% to 5.7% for concrete prisms with aspect ratio 1: 1 of grades 25 and 30 respectively. After which, the measured UPV values reduced significantly under a higher compressive stress of up to 0.5 stress-strength ratio, with a reduction of about 6.9% to 7.3% for concrete prisms with aspect ratio 1: 1 of grades 25 and 30 respectively at the age of 28 days. These results show that compressive stress in concrete has significant effect on the measured UPV values. This implies that the state of stress in concrete has to be determined first when UPV is used for the estimation of in-situ concrete strength. Otherwise, if in-situ UPV values are used to estimate the in-situ concrete strength by using the correlated results based on stress free concrete in the laboratory, the in-situ concrete strength may be underestimated, in particular ifthe state of stress is more than 0.25 stress-strength ratio.